The Anxiety and Defense Mechanism of Gilmore in Happy Gilmore Movie - Siregar, Rusnandar; Astuti, Anjar Dwi; Muhajir, Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
ABSTRACTHappy Gilmore is a movie that tells the story of Gilmore whose ambition was to become a professional hockey player. However, he had to leave it to find money to pay for his grandmother's house. Then, he jumped into golf tournaments because he could raise money quickly. In his struggle, Gilmore must experience a lot of anxiety and he must fight these feelings to achieve his goals. The first purpose of this study is to determine the type of anxiety experienced by Gilmore in the Happy Gilmore movie (1997). Besides, this study also aimed to determine the type of defense mechanism Gilmore used to overcome his anxiety. This study was qualitative research because it focused on analyzing the psychological aspect of a character in a movie. Accordingly, the approach used here was the psychological approach. In this study, the researcher used Freud's theory about anxiety and defense mechanisms. Based on the results of the study, it was found that Gilmore experienced neurotic anxiety, moral anxiety, and realistic anxiety. To overcome his anxiety, Gilmore used several types of defense mechanisms. These defense mechanisms were sublimation, displacement, projection, rationalization, reaction formation, regression, denial, and compensation. Keyword: Anxiety, Defense Mechanism, Happy Gilmore movie